Biomass, biofuels, biochemicals : biochemicals and materials production from sustainable biomass resources - Li, Hu; Saravanamurugan, S.; Pandey, Ashok; Elumalai, Sasikumar (Elsevier, 2022)
Biochemicals and Materials Production from Sustainable Biomass Resources provides a detailed overview of the experimentally developed approaches and strategies that facilitate carbon-based materials and fine chemicals derivation from biomass feedstocks with robust catalyst systems and renewed conversion routes. In addition, the book highlights theoretical methods like techno-economic analysis of biobutanol synthesis. As academia and industry are now striving to substitute fossil-based chemicals with alternative renewable resources, second-generation lignocellulosic biomass which does not depend on the food cycle has become increasingly important. Lignocellulosic biomass is composed of three major polymeric components - lignin, cellulose and hemicellulose. The polymers can be degraded into monomeric counterparts through selective conversion routes like hydrolysis of cellulose to glucose and of hemicellulose to xylose.